2014
DOI: 10.1017/s1368980014002183
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hyperthyroidism according to type of vegetarian diet

Abstract: Objective Vegetarian diets may be associated with low prevalence of autoimmune disease, as observed in rural sub-Saharan Africans. Graves’ disease, an autoimmune disorder, is the most common cause of hyperthyroidism. We studied prevalence of hyperthyroidism according to dietary pattern in a population with a high proportion of vegetarians. Design Cross-sectional prevalence study. The association between diet and prevalence of hyperthyroidism was examined using multivariate logistic regression analyses contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…The authors reported an association of vegan diet and lower risk of hypothyroidism [ 7 ]. The same group of authors also showed that vegan and vegetarian diets are associated with lower risk of hyperthyroidism [ 8 ]. The authors suggest a possible protective effect of polyphenols (such as flavonoids) against autoimmune processes, but a detailed explanation on the molecular level is not provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported an association of vegan diet and lower risk of hypothyroidism [ 7 ]. The same group of authors also showed that vegan and vegetarian diets are associated with lower risk of hyperthyroidism [ 8 ]. The authors suggest a possible protective effect of polyphenols (such as flavonoids) against autoimmune processes, but a detailed explanation on the molecular level is not provided.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no comprehensive studies investigating dietary habits and their influence on AITD to date. Only two studies analysed the prevalence of self-reported hypothyroidism and hyperthyroidism in relation to dietary habits, and found a protective effect of vegan diet from hypothyroidism, and both vegan and vegetarian diets from hyperthyroidism [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within the last decades, plant‐based nutrition has experienced increased interest in the medical community. Plant‐based diets may reduce the likelihood of many traditional risk factors that are associated with AF, including hypertension, hyperthyroidism, obesity, and diabetes . Moreover, plant‐based nutrition may also positively affect emerging risk factors, such as inflammation or subclinical atherosclerosis.…”
Section: Risk Factor Modification Through Dietary Modificationmentioning
confidence: 99%
“…Plant-based diets may reduce the likelihood of many traditional risk factors that are associated with AF, including hypertension, hyperthyroidism, obesity, and diabetes. 34 Moreover, plant-based nutrition may also positively affect emerging risk factors, such as inflammation or subclinical atherosclerosis. Current evidence supporting these statements is present below and in Table 1.…”
Section: Ris K Fac Tor Mod Ifi C Ati On Throug H Die Tary Modific Amentioning
confidence: 99%
“…Interestingly, a recent paper showed a low risk of hyperthyroidism in people following a vegan, lacto-ovo and pesco vegetarian diets compared with omnivores [70].…”
Section: Dietary Habitsmentioning
confidence: 99%